Understanding the contributions of the Treatment Action Campaign and Section27 to a Rights-Based Approach to HIV and AIDS in South Africa - Dlamini, Nomalanga (Rhodes University, Faculty of Humanities, Department of Sociology, 2017)
This thesis examines the link between social movements with the legal system to enforce human rights within the public health sector in regards to access to HIV and AIDS-related disease treatment. Research shows large scale incapacity for the provision of such essential medications within the public health sector; this is not merely an issue for those in the developing world. This thesis demonstrates that it is an issue that is faced by those using the public health sector services to access essential HIV and AIDS medications and it shows that certain people are unaware of their human rights to have fair and equal access to such essential medications. Although there is abundant research studies on HIV and AIDS in South Africa, there is a lack of studies that look into the impact that social movements have had in strong-arming, to a certain extent, the government in holding it accountable for infringing its constitutional promises to all citizens. This thesis is set against a backdrop where, the crisis of lack of access to essential medications in the public health sector which is closely intertwined with the collapsing health care system and it is combined with the issues of international patent policy for essential medication and developing countries like South Africa, who are trying to tackle this hurdle straight on. This thesis argues that the social injustices of rights violations integrated with the issues of international patent laws aggravate the access to essential medications in the public health sector in the country. This thesis adopts the use of a Rights-Based Approach, which is built on the foundational understanding that at the centre the focus is on human rights. In using the rights-based approach the intention is to outline ways in which to improve and further develop the ability of individuals and communities to recognize their rights. The findings show that the important factor of using a Rights- Based Approach is that it puts the pressure on the state to legitimately fulfil its obligation to its people. Thus the thesis evaluates the use of combining the legal system to enforce human rights and the role of social movements to realize the right to health for South Africans that use the public health sector to access essential HIV and AIDS antiretroviral drugs. This research paper shows that the Treatment Action Campaign and Section27 have contributed to the recent transformation of the public health sector in South Africa. They have achieved this through the implementation of rights-based education campaigns as well as HIV and AIDS education particularly geared for those that use the public health sector facilities, to attain access to essential medications; not only for HIV and AIDS but also for tuberculosis and other AIDS-related disease treatment. The thesis further highlights that the Treatment Action Campaign and Section27 have assisted in greatly improving the access to HIV and AIDS essential medications for prevention of Mother to Child Treatment Programs. The findings of the research paper outline that the main issue lies in the fact that even though essential medications for HIV and AIDS are now more available, the medical infrastructure is one of the main problems accounting for the lack of service delivery of these essential medications in the country's public health sector.
Keywords: Treatment Action Campaign; SECTION27 (Braamfontein, -- South Africa); AIDS (Disease) -- Prevention -- South Africa; AIDS (Disease) -- Law and legislation -- South Africa; Public health laws -- South Africa; AIDS (Disease) -- Patients -- Legal status, laws, etc. -- South Africa; AIDS (Disease) -- Patients -- Civil rights -- South Africa